The Use of Chat GPT in ELT - Ira Irzawati; Agnes Felisya Unamo; Agnes Agnes; Vinny Angelika (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2024)
As Chat GPT rose to fame rapidly, it has drawn attention of researchers around the globe to conduct studies related to the use of Chat GPT in various sectors including education. This study aims to investigate the use of Chat GPT in ELT through reviewing numerous previous related journal articles. In this review study, the researchers collected thirty journal articles from several primary online databases, such as: ERIC, Google Scholar, Sage Pub, ProQuest, Elsevier, Academia, and Research Net. To analyze the data, the researchers performed a set of procedures, namely data selection, classification, analysis, and conclusion. The results indicate that Chat GPT is a powerful tool that potentially brings benefits yet it requires more consideration and caution to be properly and effectively implemented. In a nutshell, the role of human resources is required to remain dominant and Chat GPT is probably used as a supporting element in ELT. It is expected that this study provides fruitful insights that are highly beneficial to promote proper understanding and implementation of Chat GPT in ELT.